This is My Life: The Stories of Independent Workers in the Creative Industries in the Netherlands - Hermes, Joke; Koch, Karel; Bakhuisen, Nicolette; Borghuis, Pauline (Javnost-The Public, 2017)
The new precariat or free agents? Two powerful stories dominate discussion of labour in what are now called the creative industries. A policy invention, the creative industries in the Netherlands combine media, the arts, cultural heritage and creative business services as a new top sector, expected to boost the national income. A large number of workers in the creative industries do so freelance, or as the Dutch have it as Independents without Personnel. We prefer to call them independent professionals. The combination of the digitalisation of work and its casualisation as a result of outsourcing by corporate firms, non-governmental organisations and governments created wholly new labour conditions. Over the past three years more than 90 interviews with independent workers in the creative industries have been conducted. This article presents the world of work from their perspective. The article will show how independent workers are carving out identities that focus on freedom, passion and work–life balance. “Maker freedom” and “a new barter economy” are the two dominant themes in the analysis of the interview material. As analysts and educators we need to attend to new discourses of artisanal and political identity construction among higher-educated workers in the creative industries.